Recent variations in the Uruguayan higher education system: a belated and diffuse path to diversification with state control and private participation (Praxis Educativa, 2023)
In this paper we try to analyze some recent and ongoing changes that are taking place in the Uruguayan higher education system. Based on a system historically conditioned by the presence of a single public university, we try to briefly review the changes at this educational level in recent years, hand in hand with different national governments. In a regional scenario of increasing privatization from which Uruguay was apparently on the sidelines at times, we examine the characteristics of some changes that are taking place now and may constitute advances in a certain wave of privatization. We use contributions from the educational field, higher education and public policies and we conclude the text problematizing how novel these changes are and their possible impact given certain national characteristics.
Keywords: higher education system; Uruguay; university policies; State; privatization